2007
DOI: 10.1021/nn700171x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Nanotube-Based Needle Nanoprobes for Electrochemical Studies in Picoliter Microenvironments

Abstract: We report the fabrication and characterization of individual nanotube-based, long and straight needle nanoprobes for electrochemistry and the study of their applicability and behavior in microenvironments. The needle nanoprobe, with a nanoscale ring-shaped Au electrode at the tip of the needle serving as the active electrode, was characterized by electrochemical current measurement and cyclic voltammetry and analyzed with electrochemical models. Such a needle nanoprobe, in combination with another metal-coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 56 publications
5
61
0
Order By: Relevance
“…The first one, essentially developed in view of the detection of small numbers of molecules released by single cells, consists in the immersion of needle-type micro-electrodes in small chambers, or vials, prepared by micro-fabrication techniques [2,3,13,14]. Alternatively, the second route deals with the immersion of needle-type micro-electrodes within droplets, or meniscus, thus avoiding the preparation of containers [15,16,17]. This approach has been implemented with micro-, nano-, picoand femto-liter droplets deposited either on a substrate or onto the electrode itself.…”
Section: Introductionmentioning
confidence: 99%
“…The first one, essentially developed in view of the detection of small numbers of molecules released by single cells, consists in the immersion of needle-type micro-electrodes in small chambers, or vials, prepared by micro-fabrication techniques [2,3,13,14]. Alternatively, the second route deals with the immersion of needle-type micro-electrodes within droplets, or meniscus, thus avoiding the preparation of containers [15,16,17]. This approach has been implemented with micro-, nano-, picoand femto-liter droplets deposited either on a substrate or onto the electrode itself.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the achievable density of nanotubes in the v-SWCNT templates is an order of magnitude greater than the best density reported to date for planar configurations-assuming a channel length of 100 nm and an additional loss of 1 ”m 2 for contact metallization in the planar geometry. Other benefits include the ability to use these v-SWCNT templates for fabricating surround-gated vertical CNTFETs [30], [31], creating ordered arrays of v-SWCNTs of adjustable density, or even using the v-SWCNT tips as probes for biological interfacing [32]. A recent modeling study [31] has shown that the presence of a gate underlap (which would be difficult to avoid in a vertical CNTFET geometry) actually suppresses ambipolar conduction and enables I-V characteristics better suited for digital applications.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, since it was difficult to properly fashion and shield the metal tips for intracellular recording, the use of metal electrodes was initially limited to extracellular recording. However, Yum et al (2007) recently demonstrated electrochemical detection in small aqueous drops (10 lm in diameter) using metal, ring-shaped nanoelectrodes.…”
Section: Metal Electrodesmentioning
confidence: 99%